Rancangan Model Pembelajaran Inquiry-based Mathematical Literacy untuk mendorong Berpikir Kritis - Syaiful Huda; Siti Mawaddah; Rivatul Ridho Elvierayani (DIDAKTIKA, 2022)
Critical thinking skills are part of higher-order thinking skills that need to be developed. Many strategi have been given by researchers in the field of mathematics. Newton and Tonelli (2020) provide inquiry-based mathematics lessons (inquiry) to overcome the problems of learners who struggle in the face of students' understanding in the field of mathematics. The learning and inquiry process itself has been widely developed to improve critical thinking skills. The purpose of this development research is to develop an inquiry-based mathematical literacy learning model to encourage critical thinking. From the results of the needs analysis and conceptual design, an inquiry-based mathematical literacy (IBML) learning model design was obtained that pays attention to the IBL model and the type of inquiry will be tested on the design made.